1-Bromopropane induces mitochondrial damage and lipid metabolism imbalance in respiratory epithelial cells through the PGC-1α/PPARα pathway - Qiuyun Wu; Chunmeng Jin; Xue Liu; Qianyi Zhang; Biyang Jiao; Hongmin Yu (Ecotoxicology and Environmental Safety)
1-Bromopropane (1-BP) has become a new air pollutant in occupational and living environments due to its advantages in industrial applications and as a representative compound of volatile organic compounds (VOCs). As an irritant, its damaging effects on respiratory epithelium are worthy of further study. This study aimed to explore the damage effects of 1-BP on respiratory epithelial cells and reveal its underlying mechanisms. We found that exposure to 1-BP markedly reduced the viability of respiratory epithelial cells in a dose-dependent manner, and induced oxidative stress and vacuolation changes in respiratory epithelial cells. Subsequently, through RNA-seq analysis, we identified that the 1-BP-induced damage of respiratory epithelial cells was related to the mitochondrial function pathway and further verified that 1-BP caused mitochondrial damage of respiratory epithelial cells, which was manifested as ultrastructural damage, decreased membrane potential, ATP, and MFN2 levels. These damages were associated with cellular oxidative stress responses. Pretreating cells with the agonists of PGC-1α and PPARα, we revealed that 1-BP affected the expression of PGC-1α and interfered with its coactivator PPARα levels, causing an increase in the expression of lipid-producing genes and a decrease in the expression of lipid-decomposing genes, thus leading to a lipid accumulation in respiratory epithelial cells. Meanwhile, the imbalance of lipid metabolism in respiratory epithelial cells induced by 1-BP further caused mitochondrial damage, and the effect was bidirectional. These findings suggested that 1-BP has a potential role in inducing respiratory epithelial cell damage and is associated with the PGC-1α/PPARα signaling pathway.